A new species of Acanthobothrium (Eucestoda: Onchobothriidae) in Aetobatus cf. narinari (Myliobatidae) from Campeche, México - Rodríguez-Ibarra,Erick (2018)
Abstract The helminthological examination of nine individuals of Aetobatus cf. narinari (spotted eagle ray; raya pinta; arraia pintada) revealed the presence of an undescribed species of cestode of the genus Acanthobothrium. The stingrays were collected from four locations in México: Laguna Términos, south of Isla del Carmen and the marine waters north of Isla del Carmen and Champotón, in the State of Campeche, and Isla Holbox, State of Quintana Roo. The new species, nominated Acanthobothrium marquesi, is a category 3 species (i.e, the strobila is long, has more than 50 proglottids, the numerous testicles greater than 80, and has asymmetrically-lobed ovaries); at the present, the only category 3 species that has been reported in the Western Atlantic Ocean is Acanthobothrium tortum. Acanthobothrium marquesi n. sp. can be distinguished from A. tortum by length (26.1 cm vs. 10.6 cm), greater number of proglottids (1,549 vs. 656), a larger scolex (707 µm long by 872 µm wide vs. 699 µm long by 665 µm wide), larger bothridia (626 µm long by 274 µm wide vs. 563 µm long by 238 µm wide). This is the first report of a species of Acanthobothrium from the Mexican coast of the Gulf México.